Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
Let p (x) = x + 1 / x = 2
= x + 1 = 2x
= 2x - x = 1
or, x = 1.
let g(x) = x^3 + 1/x^3
since, x = 1
therefore,
g (1) = (1)^3 +1 / (1)^3
= 1 + 1 / 1
= 2 / 1
= 2
So, the answer to your question is 2.
x + 1 / x = 2
x × ( x + 1 / x ) = x × 2
x + 1 = 2x
x - x + 1 = 2x - x
x = 1
_________________________________
x^3 + 1 / x^3 =
1^3 + 1 / 1^3 =
1 + 1 / 1 =
2 / 1 =
2
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.